Comparison of Mini-Micro LNG and CNG for Commercialization of Small Volumes of Associated Gas - Tractebel Engineering (World Bank, Washington, DC, 2017)
The Global Gas Flaring Reduction Partnership (GGFR) provides its members with overviews of the potential solutions to recover and monetize the flared and/or associated gas. The purpose of this report is to compare the Liquefied Natural Gas (LNG) and Compressed Natural Gas (CNG) chain concepts that could be used to monetise small volumes (1-15MMscf/d) of associated gas and avoid or reduce the current gas flaring. Both LNG and CNG concepts have been developed for over 50 years in similar though not exactly the same ways, and have gained some maturity as a result of the gas market expansion. The CNG and LNG reports analysed the available technologies and the development of the respective chains in specific countries for a better understanding of the mechanism of their evolution and for possible application in other emerging countries. This report will compare both CNG and LNG chain concepts for small volumes monetisation and will identify the drivers that could increase their implementation to reduce gas flaring and its consequential emissions.